Baseline Prostate-Specific Antigen Levels in Midlife Predict Lethal Prostate Cancer - Preston, Mark A.; Batista, Julie L.; Wilson, Kathryn M.; Carlsson, Sigrid V.; Gerke, Travis; Sjoberg, Daniel D.; Dahl, Douglas M.; Sesso, Howard D.; Feldman, Adam S.; Gann, Peter H.; Kibel, Adam S.; Vickers, Andrew J.; et al. (Journal of clinical oncology, 2016)
Prostate-specific antigen (PSA) level in midlife predicted future prostate cancer (PCa) mortality in an unscreened Swedish population. Our purpose was to determine if a baseline PSA level during midlife predicts lethal PCa in a US population with opportunistic screening. We conducted a nested case-control study among men age 40 to 59 years who gave blood before random assignment in the Physicians' Health Study, a randomized, placebo-controlled trial of aspirin and β-carotene among 22,071 US male physicians initiated in 1982 and then transitioned into a prospective cohort with 30 years of follow-up. Baseline PSA levels were available for 234 patients with PCa and 711 age-matched controls. Seventy-one participants who developed lethal PCa were rematched to 213 controls. Conditional logistic regression was used to estimate odds ratios and the area under the receiver operating characteristic curve, with 95% CIs, of the association between baseline PSA and risk of lethal PCa. Median PSA among controls was 0.68, 0.88, and 0.96 ng/mL for men age 40 to 49, 50 to 54, and 55 to 59 years, respectively. Risk of lethal PCa was strongly associated with baseline PSA in midlife: odds ratios (95% CIs) comparing PSA in the > 90th percentile versus less than or equal to median were 8.7 (1.0 to 78.2) at 40 to 49 years, 12.6 (1.4 to 110.4) at 50 to 54 years, and 6.9 (2.5 to 19.1) at 55 to 59 years. A total of 82%, 71%, and 86% of lethal cases occurred in men with PSA above the median at ages 40 to 49, 50 to 54, and 55 to 59 years, respectively. PSA levels in midlife strongly predict future lethal PCa in a US cohort subject to opportunistic screening. Risk-stratified screening on the basis of midlife PSA should be considered in men age 45 to 59 years.